Student Views of Ethics Position in Business (Comparison Among Students of Accounting, Management, and Economic Development Department) - ., Sunaryanto; Achadiyah, B N; Rafsanjani, M A; Priyono, A; Kurnianti, D; Yuliani, E (KnE Social Sciences, 2018)
Generally, normative ethics has two main categories, namely teleology and deontology. Teleology covers all views expressing a care to the expected consequences of an action, while deontology focusing on the need to follow a certain rule. This study aimed in exploring the views of students toward the position of ethics in business using those two main categories. This study compared three groups of students from three departments: accounting, management and economic development. This study also focused on the effect of study period toward student’s views related with the position of ethics in business. By using one way ANOVA and independent t test, it can be implied that there was a significant difference of student’s views toward the position of ethics in business among students from accounting, management, and economic development. Moreover, the Tukey test showed that there was a significant difference of student views toward the position of ethics in business between accounting and management students (sig 0.018 < 0.05), while there was no significant difference of student’s views toward the position of ethics in business between accounting and economic development students (sig 0.992 > 0.05). Differently, there was a significant difference of student’s views toward the position of ethics in business between management and economic development students (sig 0,013 < 0.05). In details, the result of this study also implied that there was no significant difference of student’s views toward the position of ethics in business among students of year 2014 and 2016, from all three departments. It implied that the study period did not affect the student’s views toward the position of ethics in business. Keywords: ethic, teleology, deontology